(untitled) (NAU Journal of Technology and Vocational Education, 2024)
The study was undertaken to determine supervisors’ ratings of the extent computer skills are possessed by secretaries for effective work performance in colleges of education in Delta State. The study adopted the survey research design and was guided by four research questions while four null hypotheses were tested at 0.05 level ofsignificance. The entire population of 132 supervisors (deans, heads of departments and directors of programmmes) in the four colleges of education in Delta State was used for the study. A 40 item structured questionnaire with five response options was used for data collection. The questionnaire was validated by three experts and its reliability co-efficient of 0.86 was calculated using Pearson Product Moment Correlation. Data relating to the research questions were analyzed using mean and standard deviation while analysis of variance (ANOVA) was used to test the four null hypotheses. The study found that secretaries in colleges of education in Delta State possessed word processing skills, electronic spreadsheet skills, internet application skills and power-point presentation skills at a moderate extent. Respondents’ mean ratings were not significantly influenced by their qualifications and designations. Based on the findings, it was concluded that the moderate possession of computer skills by secretaries in colleges of education in Delta State may be affecting their effective performances in the present technology driven era. It was recommended among others that authorities of colleges of education in Delta State should regularly organize retraining programmes for secretaries on the usage of computer and its applications.